Effect of supercritical CO2 extraction on pore characteristics of coal and its mechanism - Chen, Run; Hu, Kunpeng; Lv, Fengrong; Zhang, Yajun (Frontiers in Earth Science, 2023)
The pore in coal is not only the place of coalbed methane accumulation, but also the pathway of gas migration. In this paper, five sets of coals before and after the second coalification were selected from the eastern margin of Ordos Basin. Mercury intrusion porosimetry and nuclear magnetic resonance tests(NMR) were used to compare the changes of pore structure and porosity due to the supercritical CO2(Sc-CO2) extraction, to discuss the evolution of pore characteristics change with coal rank because of Sc-CO2 extraction, and to explain the mechanism. The results show that: (1) Pore volume, pore specific surface area and connectivity characteristics were changed significantly by Sc-CO2 extraction, and the increment of pore volume and pore specific surface area presents a law of increase-decrease-increase with coal rank increasing, the turning point is near the second coalification. (2) The porosity increment change due to Sc-CO2 extraction was increased-decreased-increased with coal rank increasing, the turning point is also near the second coalification, which supports the mercury intrusion porosimetry results. (3) The changes of porosity characteristics due to Sc-CO2 extraction through pore increasing and expanding effects, the pore increasing and expanding effects co-exist in the micropore and before the second coalification, the pore expanding effect is mainly exist in above transitional pore and after the second coalification. (4) The pore structure change model of coal due to Sc-CO2 extraction was established. The conclusions not only have important theoretical significance for CO2-ECBM mechanism, but also have important significance for CO2-ECBM engineering.